The Influence of Leadership, Compensation on Work Motivation and its Impact on Employee Work Productivity - Djunaedi Djunaedi; Arief Karimauv; Sylvia Kartika Dhamayanti; Aulia Nurlaili Kusuma Wardani; Hadi Purnomo (International Journal of Economics Development Research (IJEDR), 2024)
The purpose of this research is to examine the influence of leadership and compensation on work productivity with motivation as a mediating variable at PT ABC Jakarta. Data were collected through questionnaires distributed to all employees of PT ABC Jakarta. The sensue technique was used for sampling and the number was 72 employees. The path analysis method was used to analyze the data. The results of this research indicate that leadership, compensation and motivation have a significant effect on work productivity at PT ABC Jakarta, while motivation is able to mediate the influence of leadership and compensation on work productivity at PT ABC Jakarta. The results of this study can be used as a reference for further researchers who will study similar problems. udy similar problems.